Factors that influence employee motivation at Melaka International College of Science And Technology (MiCoST) / Nur Syahidah Mohamad Zahidi - Mohamad Zahidi, Nur Syahidah (Faculty of Business and Management, 2019)
This research is about the factors that influence employee motivation at Melaka International College of Science and Technology (MiCOST). The purpose of this research is to determine how can reward and other incentives can influences employee motivation in Melaka International College of Science and Technology (MiCOST), to find out the relationship between job security and employee motivation and lastly to examine how leadership style can influence employees motivation. Based on this research, there are three factor that influence to employee motivation which are reward and other incentive, job security and leadership style (transformational and transactional). This research represents motivation at Melaka International College of Science and Technology (MiCOST). Only 92 respondents were selected using simple random sampling out of 120 employees. Based on this research, reward and other incentive shows the most significant relation which means reward and other incentive factors that influence the most on employee motivation in Melaka International College of Science and Technology (MiCOST).